2012
DOI: 10.1177/0748730411434384
|View full text |Cite
|
Sign up to set email alerts
|

Or47b Receptor Neurons Mediate Sociosexual Interactions in the Fruit Fly Drosophila melanogaster

Abstract: In the fruit fly Drosophila melanogaster, social interactions especially among heterosexual couples have been shown to have significant impact on the circadian timing system. Olfaction plays a major role in such interactions; however, we do not know yet specifically which receptor(s) are involved. Further, the role of circadian clock neurons in the rhythmic regulation of such sociosexual interactions (SSIs) is not fully understood. Here, we report the results of our study in which we assayed the locomotor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 33 publications
4
37
1
Order By: Relevance
“…Such nocturnality was not observed in male-male pairs or female-female pairs (Figure 1B, C). This observation is consistent with those of previous studies [16,29]. To determine whether the nocturnality in male-female pairs is mediated by the circadian clock, we paired male and female per 01 arrhythmic mutants, in which the circadian feedback loops stop due to the lack of a functional per gene [31].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Such nocturnality was not observed in male-male pairs or female-female pairs (Figure 1B, C). This observation is consistent with those of previous studies [16,29]. To determine whether the nocturnality in male-female pairs is mediated by the circadian clock, we paired male and female per 01 arrhythmic mutants, in which the circadian feedback loops stop due to the lack of a functional per gene [31].…”
Section: Resultssupporting
confidence: 88%
“…Because we used a conventional activity recording system, the activity of each male and female fly was pooled, as in a previous study [29]. Individual flies displayed typical bimodal activity patterns with peaks in the morning and evening (Figure 1A, red and blue, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that Gr5a-GAL4 do not overlap with markers for pheromone-sensing GRNs (ppk23, ppk25, and fru M ) [10], [14], and that Gr5a + GRNs did not respond to male pheromones [20]. Furthermore, disruption of Gr5a + function does not decrease aggression when the aggression promoting resource is females instead of food (Figure S8a), nor does it produce any effect on courtship or social behaviors [18], [75]. Finally, disruption of Gr5a + GRNs function decreases aggression in the presence of sucrose (Figure S8c).…”
Section: Discussionmentioning
confidence: 84%
“…Or47b and Or67d showed higher expression levels in male flies, while Or59b, Or9a, and Obp19b showed higher expression levels in female flies. Or47b and Or67d were proposed as being involved in sociosexual interactions in flies, such as courtship and mating behaviors (Lone and Sharma 2012). In particular, the ablation of Or47b neurons had the most dramatic effect on the sociosexual interaction behaviors (Lone and Sharma 2012).…”
Section: Sex-biased Chemosensory Genes In Adult Antennaementioning
confidence: 99%
“…Or47b and Or67d were proposed as being involved in sociosexual interactions in flies, such as courtship and mating behaviors (Lone and Sharma 2012). In particular, the ablation of Or47b neurons had the most dramatic effect on the sociosexual interaction behaviors (Lone and Sharma 2012). Using microarrays, Kopp et al (2008) found 406 differentially expressed genes between male and female antennae among 9,830 genes examined, including 20 Or and Obp genes (with a FDR of <0.2).…”
Section: Sex-biased Chemosensory Genes In Adult Antennaementioning
confidence: 99%